college algebra, Please help!!

solve the following logarithmic equation

2log2(lower than g)^(x-2)+log2^2=3


  1. 👍 0
  2. 👎 0
  3. 👁 40

Respond to this Question

First Name

Your Response

Similar Questions

  1. Urgent math

    i need help with these two homework problems Use the Laws of Logarithms to combine the expression into a single logarithm log2 5 − 5 log2 x + 1/2 log2(x + 1) Solve the logarithmic equation for x log2(x + 2) + log2(x − 1) = 2

    asked by Emma on August 3, 2015
  2. math

    solve the equation log2(x+4)-log4x=2 the 2 and 4 are lower than the g This is what I got: log2(x+4)+log2(4^x)=2 log2((x+4)*4^x)=2 4^x(x+4)=4 x=0 is a solution???

    asked by anonymous on January 9, 2013
  3. Calculus

    Find the area cut off by x+y=3 from xy=2. I have proceeded as under: y=x/2. Substituting this value we get x+x/2=3 Or x+x/2-3=0 Or x^2-3x+2=0 Or (x-1)(x-2)=0, hence x=1 and x=2 are the points of intersection of the curve xy=2 and

    asked by MS on April 1, 2014
  4. precalc

    Solve the logarithmic equation for x. (Enter your answers as a comma-separated list.) log2(x + 17) − log2(x − 2) = 1 2 is the base for the log.

    asked by JB on March 7, 2016
  5. Algebra

    Solve the logarithmic equation. log2(4x)-log2(x+3)=1

    asked by Meghan on July 29, 2011
  6. math30

    1.Use the laws of logarithms to express log2 (6) – log2 (3) + 2log2 (8)^1/2 as a single logarithm; then evaluate. 2. For logy = log(0.5x – 3) + log2, express y as a function of x.

    asked by alejandro on July 10, 2012
  7. math

    Can someone solve this and explain it please 4^log2 (2log2 5)

    asked by Chuck on May 23, 2011
  8. Math

    log2(-3sinx)=2log2(cosx)+1 solve for x

    asked by Sarah on January 12, 2016
  9. Math

    Hello! Could someone please take a look at the problem below and let me know if I made mistakes in simplifying the given equation? I'm quite certain that I did make a mistake somewhere because the original equation and its

    asked by Constantine on May 31, 2015
  10. Logarithms

    I'm working on logarithmic equations and I'm stuck on how my book arrives at the next step. First, they use the change of base formula on, log(sqrt(2))(x^3 - 2) (sqrt(2)) is the base,changing to base 2 log(sqrt(2))(x^3 - 2)=

    asked by Helper on March 9, 2011

More Similar Questions